(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
The purpose of this study was to compare the reported use of writing strategies of Iranian EFL learners in two different venues of technology-assisted and conventional writing classes. Overall, thirty two EFL students participated in this study, eighteen in a technology-assisted and fourteen in a conventional English class who responded to a 64-item Likert scale writing strategy inventory adapted from Wei and Chen (2004) and Griffiths and Jordan (2005). The results of the independent sample t-tests revealed that there was a statistically significant difference between the reported use of language-related writing strategies. The results of the paired-sample t-tests, in addition, demonstrated that just in the technology-assisted environment, there was a statistically significant difference for the constructs of language-related and organization strategies and writing experience. The results of this study could carry significant implications for technology-assisted writing instruction in EFL contexts.